Degradation Mechanism of Vanadium Oxide Films When Grown on Y‐Stabilized ZrO2 Above 500 °C. Issue 12 (16th October 2019) - Choi, Songhee; Oh, Junhyeob; Lee, Ji-Hyun; Jang, Jae Hyuck; Lee, Shinbuhm
Abstract : Although vanadium oxide (VO x ) phases are thermodynamically similar, Y‐stabilized ZrO2 (YSZ) substrates show selective growth as single‐crystalline films. However, in this study, we find that the films degrade with the formation of nanoislands when evaporating VO x onto YSZ at a substrate temperature >500 °C. The nanoislands are epitaxial, i.e., Y‐doped VO2 (R) at an oxygen partial pressure P O 2  < 30 mTorr, and YVO4 at P O 2  > 50 mTorr. Energy‐dispersive X‐ray spectroscopy shows that the rapid diffusion of vanadium and yttrium plays a critical role in film degradation. The degradation mechanism revealed herein guides the fabrication of VO x films for energy and electronic device applications. Abstract : The degradation of vanadium oxide films occurs with the formation of nanoislands when depositing the films onto Y‐stabilized ZrO2 at a substrate temperature >500 °C. The rapid diffusion of vanadium and yttrium plays a critical role in film degradation. The degradation mechanism guides the fabrication of vanadium oxide films for energy and electronic device applications.